Preliminary study on the presence of bee diseases in swarms of Africanized honey bees (Apis mellifera) in different areas of Costa Rica - Calderón, Rafael A. (2019)
The presence of bee diseases was studied in 34 swarms of Africanized honey bees, recently established in different geographic areas of Costa Rica. One hundred adult bees were collected from the brood chamber of each swarm in a plastic container containing 70.0% alcohol to preserve them until the analysis. Bees were processed at the Bee Pathology Lab of the Tropical Beekeeping Research Center (CINAT-UNA), where samples were tested for varroosis, nosemosis, and acariosis. Based on the study conducted, recently established swarms of Africanized honey bees had the presence of varroosis and nosemosis, but no acariasis. From the samples that tested positive for varroosis, 41.0% showed a low level of infestation, with 2.0 ± 0.05 (mites/100 bees), while only 6.0% had a high level. In addition, from the samples that tested positive for Nosema spp, 26.0% showed a very low level of infection, while 18.0% had a low level. No high or moderate levels of infection were observed for Nosema spp. Given that most beekeepers catch and introduce swarms directly to the apiary, they are recommended to quarantine swarms and make laboratory analyses to know their health condition. This will allow for immediate actions to control diseases and, consequently, prevent contamination of healthy colonies in the apiary.